Computer Business. - Achor, John (Writers' Journal)
The article offers tips for writers on how to operate Windows XP and Word 2003. Writers need to keep their hands on keyboard instead of jumping to the mouse and back. It is noted that the Tab key will move through a dialog box from top left to bottom right. Writers should type at the first dialog box text entry and hit Tab to move to the next entry point.